SMS Advertising and Its Relationship with Customer Purchase Intention of Value Added Services (Global Journal of Management and Business Research, 2019)
The main endeavor of the present study was to know the relationship between SMS (Short Message Service) advertising and customer purchase intention of value-added services (VAS) of mobile operators. This study was descriptive in nature. The population of the study was the users of mobile phone from two wards of Rajshahi City Corporation were purposively selected. Respondents were selected using convenience sampling method for collecting primary data through a self-administrated questionnaire. 142 completely filled up questionnaires were authentic for the research study. Five factors of SMS advertisement were considered as independent variables to evaluate the respondents' opinion. Study results show that the maximum number of respondents strongly agree that SMS advertising provides current information to them, the company provide actual information through SMS advertisement, SMS advertisement is funny, exciting, reliable, personalize, entertaining and trustful but too much advertising is irritating and disturbing. Result also shows that there is a positive significant correlation between the variables and the highest correlation exist annoyingness to SMS advertisement and customer purchase intention of valueadded services of mobile operators (r = .813**, p=.000
Keywords: purchase intention; SMS advertisement; value added service; entertainment; personalization